Polyomavirus Large T Antigen Binds Cooperatively to Its Multiple Binding Sites in the Viral Origin of DNA Replication - Peng, Yu-Cai (American Society for Microbiology, 1998)
Polyomavirus large T antigen binds to multiple 5′-G(A/G)GGC-3′ pentanucleotide sequences in sites 1/2, A, B, and C within and adjacent to the origin of viral DNA replication on the polyomavirus genome. We asked whether the binding of large T antigen to one of these sites could influence binding to other sites. We discovered that binding to origin DNA is substantially stronger at pH 6 to 7 than at pH 7.4 to 7.8, a range often used in DNA binding assays. Large T antigen-DNA complexes formed at pH 6 to 7 were stable, but a fraction of these complexes dissociated at pH 7.6 and above upon dilution or during electrophoresis. Increased binding at low pH is therefore due at least in part to increased stability of protein-DNA complexes, and binding at higher pH values is reversible. Binding to fragments of origin DNA in which one or more sites were deleted or inactivated by point mutations was measured by nitrocellulose filter binding and DNase I footprinting. The results showed that large T antigen binds cooperatively to its four binding sites in viral DNA, suggesting that the binding of this protein to one of these sites stabilizes its binding to other sites via protein-protein contacts. Sites A, B, and C may therefore augment DNA replication by facilitating the binding of large T antigen to site 1/2 at the replication origin. ATP stabilized large T antigen-DNA complexes against dissociation in the presence, but not the absence, of site 1/2, and ATP specifically enhanced protection against DNase I digestion in the central 10 to 12 bp of site 1/2, at which hexamers are believed to form and begin unwinding DNA. We propose that large T antigen molecules bound to these multiple sites on origin DNA interact with each other to form a compact protein-DNA complex and, furthermore, that ATP stimulates their assembly into hexamers at site 1/2 by a “handover” mechanism mediated by these protein-protein contacts.